Effects of China's payment for ecosystem services programs on cropland abandonment: A case study in Tiantangzhai Township, Anhui, China. (April 2018) - Zhang, Qi; Song, Conghe; Chen, Xiaodong
Abstract: Cropland abandonment has emerged as a common phenomenon in land use transitions. Both cropland abandonment and Payment for Ecosystem Services (PES) programs can facilitate the provision of ecosystem services. However, the relationship between cropland abandonment and PES programs remains poorly understood. China has recently undergone considerable cropland abandonment in mountainous areas. Meanwhile, China adopted a series of forest conservation and restoration policies under the scheme of PES starting in the late 1990s. In this study, we track the temporal trend of cropland abandonment under China's two PES programs, Conversion of Cropland to Forest Program (CCFP) and Ecological Welfare Forest Program (EWFP), in Tiantangzhai Township, Anhui Province. We use a random-coefficients logistic regression model to examine the roles that these two PES programs, together with other factors, played in cropland abandonment. Results indicate that: 1) the overall cropland abandonment rates for the CCFP-participating households were lower than those for the non-participants in the years immediately after the implementation of the CCFP, but there was an acceleration of cropland abandonment by the CCFP participants afterwards, leading to the convergence of cropland abandonment rates between the two types of households. 2) Although CCFP payment did not have a long-term effect on cropland abandonment, a larger amount of EWFP payment significantly increased the likelihood of cropland abandonment. 3) Land parcel biophysical characteristics that facilitated cropland abandonment include proximity to EWFP and CCFP forests, poor accessibility and unfavorable topographic positions, and 4) among household socioeconomic conditions, poor farm labor availability and high proportion of local off-farm income in total gross income increased the likelihood of cropland abandonment, while owning domestic animals decreased the likelihood of abandoning cropland. EWFP cash compensation (socioeconomic factors) and distances from cropland parcels to both EWFP and CCFP forest lands (geographic factors) had direct and indirect impacts on cropland abandonment, potentially facilitating the provision of ecosystem services through forest restoration and regrowth on the abandoned land. These findings are highly valuable for policy-makers designing similar PES programs with higher cost-effectiveness and better selection of croplands as targets for reforestation.